ANALYSIS OF FACTORS AFFECTING THE QUALITY OF ACCOUNTING INFORMATION SYSTEMS (CASE STUDY AT PT. NIPSEA PAINT AND CHEMICALS LTD JEMBER) - Mareta Susana; Suwignyo Widagdo; Lia Rachmawati (MBA : Journal of Management and Business Aplication, 2024)
This study aims to analyze the Education and Training Program, System User Involvement, HR Competence, and Information Technology on the Quality of Accounting Information Systems at PT. Nipsea Paint and Chemicals LTD Jember branch. This research is quantitative research by distributing questionnaires and the data analysis methods used are Validity Test, Reliability Test, Classical Assumption Test, Normality Test, Multicollinearity Test, Heteroscedasticity Test, Multiple Linear Regression Analysis, Hypothesis Test (partial and simultaneous) and Determination Test. The results of this study indicate that the Education and Training Program, System User Involvement, HR Competence, and Information Technology have a positive influence or simultaneously affect the Quality of the Accounting Information System and Information Technology partially affects the Quality of the Accounting Information System while the variables of the Education and Training Program, System User Involvement, HR Competence have a negative influence or have no partial effect on the Quality of the Accounting Information System.